Multiple Haar basis and m-term appriximations for functions from the Besov classes. I - Romanyuk, V. S. (Ukrains’kyi Matematychnyi Zhurnal, 2016)
We describe the isotropic Besov spaces of functions of several variables in the terms of conditions imposed on the Fourier – Haar coefficients.